Effects of various carbon-based materials on polymer matrix to the barrier and corrosion performance of coating - Sajor, Normie Jean B. (Animo Repository, 2022)
The modified version of the Horizontal Vapor Phase Growth (HVPG) technique has been adapted to synthesize multilayer graphene. The study investigates varying temperatures and times when layered carbon exfoliation occurs, which is determined to be 1100oC for 3 hrs. It has been confirmed through various characterization, such as morphology, elemental composition, structural properties, and crystallinity, that an amorphous multilayer graphene (graphite oxide) is formed. The optimal ratio of the multilayer graphene and commercial graphene on the PANI matrix and the composite filler material on the coating binder matrix has been analyzed through the corrosion property, algae susceptibility, and hydrophobicity tests. Results show that lower concentrations of the Polyaniline/Commercial Graphene (PANI/CG) and Polyaniline/Multilayer Graphene (PANI/MG) performed better anticorrosion properties, especially at higher concentrations, the composite material tends to agglomerate because of the Van der Waals interaction of graphene. Furthermore, the algae susceptibility test indicates that commercial graphene affects the algae since, as the formulation is increased, minimal algae attachment is observed. Unlike in the composite material using multilayer graphene, the surface roughness has been the factor in the algae attachment. The hydrophobicity test also signified that all formulations, including the 5-layer commercial corrosion coating, the PANI/CG, and PANI/MG, are hydrophilic. The factor contributing to the hydrophilic property of the 5-layer commercial corrosion coating and PANI/CG is the coating binder matrix, while for the PANI/MG, the multilayer graphene is already hydrophilic. Polysiloxane has been integrated with the coating matrix to address the hydrophobic property.